If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -39 + -12x = -7x + 26 Reorder the terms: -39 + -12x = 26 + -7x Solving -39 + -12x = 26 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -39 + -12x + 7x = 26 + -7x + 7x Combine like terms: -12x + 7x = -5x -39 + -5x = 26 + -7x + 7x Combine like terms: -7x + 7x = 0 -39 + -5x = 26 + 0 -39 + -5x = 26 Add '39' to each side of the equation. -39 + 39 + -5x = 26 + 39 Combine like terms: -39 + 39 = 0 0 + -5x = 26 + 39 -5x = 26 + 39 Combine like terms: 26 + 39 = 65 -5x = 65 Divide each side by '-5'. x = -13 Simplifying x = -13
| 4(1.5+6)-2=-9 | | m(m+6)=72 | | 73+4x=-5x-134 | | y=390+60y | | 4x^2-16x=-15 | | 72+4x=-5x-134 | | 2(w^2)-9w=0 | | y=510+60y | | -40+-6= | | 5x-34=-2x+78 | | 21x-400=x | | 112=-41+9x | | 12(3x-4)=3(12x+6) | | y=590+.60y | | 2X-1=33+X | | 10-3x=58 | | 5*0-4y=-20 | | 4x-58=-x+27 | | 6+12m-2=7m+76-3m | | -80=-5x-30 | | -6x-10=32 | | x^4+10x^3+36x^2+56x+32=0 | | -2p+8=5-(9p+6) | | -12x=288 | | m(7+m)=78 | | -47+4x=34+7x | | 12x^2y-16x^2-18y+24=0 | | 150=-7x+5(-x+6) | | 10x^2+28x-96=0 | | 8c-5c-6c= | | 6*0-5y=-30 | | -x(x-8)+2(x+2)=x+9 |